Properties and consolidation of nanostructured TiO2 by pulsed current activated sintering - Shon, In-Jin; Lee, Geon-Woo; Doh, Jung-Mann; Yoon, Jin-Kook (KOREAN ASSOC CRYSTAL GROWTH, INC, 2013)
TiO2 powders were high-energy ball milled for various durations and consolidated using the pulsed current activated sintering (PCAS). The effect of milling on the sintering behavior and crystallite size TiO2 powders were evaluated. A nanostructured dense TiO2 compact with a relative density of up to 99% was readily obtained within 1 min. The ball milling effectively refined the crystallite structure of TiO2 powders and facilitated the subsequent consolidation. The sinter-onset temperature was reduced appreciably by the prior milling for 10 h. Accordingly, the relative density of TiO2 compact increased as the milling time increases. The microhardness and fracture toughness of sintered TiO2 increased as the density increases.
Keywords: LOW-TEMPERATURE; MECHANICAL-PROPERTIES; OPTICAL-PROPERTIES; THIN-FILMS; COMPOSITE; COMPACTION; ELECTRODES; CERAMICS